2019
DOI: 10.30910/turkjans.556607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEG Induced Drought Stress on Germination and Seedling Traits of Maize (Zea mays L.) Lines

Abstract: Maize is the staple food crop in hilly areas of Nepal. Drought stress is one of the most important crop growth limiting factors leading to lower crop productivity in these areas. Maize seedlings are susceptible to drought stress. Nine lines (Arun-2, NML-1, Rampur Composite, RL-100, RL-105, Rl-106, RL-197, RML-18 and RML-8) of maize obtained from National Maize Research Program, Rampur, Chitwan, Nepal to study their tolerance to drought stress. An experiment was designed to study their drought tolerance by subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This could be a result of the negative impacts of water stress on the growth of root cells, which would impede nutrient uptake and negatively impact photosynthesis, which is necessary for biomass buildup and, consequently, shoot and root elongation. Therefore, it appears that under water stress, plants' ability to absorb and use water is reduced to the point where their droughttolerance mechanisms cannot support continued normal development (Ashaduzzaman et al, 2020;Islam et al, 2018;Magar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This could be a result of the negative impacts of water stress on the growth of root cells, which would impede nutrient uptake and negatively impact photosynthesis, which is necessary for biomass buildup and, consequently, shoot and root elongation. Therefore, it appears that under water stress, plants' ability to absorb and use water is reduced to the point where their droughttolerance mechanisms cannot support continued normal development (Ashaduzzaman et al, 2020;Islam et al, 2018;Magar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported by Batool et al [ 38 ] that 15% PEG treatments to sensitive and tolerant plants resulted in a decrease in chlorophyll (a, b, total), carotenoids, and relative water content, but an increase in enzymes such as ascorbate peroxidase, catalase, peroxidase, and superoxide dismutase. Magar et al [ 11 ] also found that PEG treatment up to −15 bars decreased germination percent, root and shoot length, fresh and dry weight, and vigor index of seedling maize. With an increase in PEG to 6%, Asghar et al [ 39 ] observed a decrease in relative water content, chlorophyll a and b , photosynthetic rates, and stomatal conductance.…”
Section: Discussionmentioning
confidence: 97%
“…Polyethylene glycol (PEG-6000) treatment can be applied to identify local maize varieties as sensitive or tolerant to drought stress before germination [ 10 , 11 ]. This method can be used to identify the best varieties for drought-prone areas and help in conservation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…" Maize is essential for global food security. The current trends of climatic changes increase water scarcity and reduce maize productivity by 15-30%" [5]. There are several abiotic factors limiting maize production in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%